2009
DOI: 10.1097/shk.0b013e31818bbe21
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Factor Xiii Diminishes Multiple Organ Dysfunction in Rats Caused by Gut Ischemia-Reperfusion Injury

Abstract: Plasma factor XIII (FXIII) is responsible for stabilization of fibrin clot at the final stage of blood coagulation. Because FXIII has also been shown to modulate inflammation and endothelial permeability, we hypothesized that FXIII diminishes multiple organ dysfunction caused by gut I/R injury. A model of superior mesenteric artery occlusion (SMAO) was used to induce gut I/R injury. Rats were subjected to 45-min SMAO or sham SMAO and treated with recombinant human FXIII A2 subunit (rFXIII) or placebo at the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Such monocyte specific chemotactic factor(s) formed during clotting could be involved in recruiting monocytes/inflammatory macrophages to the site of injury. FXIII might also affect PMN leukocytes, since neutrophils from FXIII-treated rats had lower respiratory burst activity [19].…”
Section: The Effect Of Active Fxiii On Leukocytesmentioning
confidence: 99%
“…Such monocyte specific chemotactic factor(s) formed during clotting could be involved in recruiting monocytes/inflammatory macrophages to the site of injury. FXIII might also affect PMN leukocytes, since neutrophils from FXIII-treated rats had lower respiratory burst activity [19].…”
Section: The Effect Of Active Fxiii On Leukocytesmentioning
confidence: 99%
“…[24, 25]. In vitro experiments have shown that activated FXIII is able to stabilize the endothelial barrier function and decrease endothelial permeability, presumably by interacting with extracellular matrix proteins in the paracellular spaces and/or minimizing disruption of adherens junctions, the protein complexes that occur at cell-cell junctions [13, 15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…The vehicle (1.0 mL/kg) or rFXIII (1.0 mg/kg) was given intravenously after 90 min of THS and re-infusion of shed blood (in THS groups) or after 90 min of TSS (in sham groups). The chosen dose of rFXIII was in alignment with the available literature data and our previous studies [13, 18]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations